The World of Art - Weiss, Paul (Carbondale, IL Illinois University press, 1961)
Paul Weiss internationally known for his searching original contributions to important philosophic problems here offers a brilliantly illuminating study of the issues at the center of art. His is one of those rare books in which a disciplined philosophic mind operates from a perceptive knowledge of the work of artists and a sensitive appreciation of modern trends.
Keywords: Esthetics; Fine art